Drought events analysis and spatial distribution for the states of Rio Grande do Norte and Paraiba, Brazil - Juliani, Bruno Henrique Toná; Pompeu, Cássia Rocha; Okawa, Cristhiane Michiko Passos (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2019)
The application of the Standardized Precipitation Index was established for 13 rain gauge stations selected in the catchment sub-basins of number 37 and 38, which correspond to the area of the states Rio Grande do Norte and Paraiba. The monthly rainfall data of the stations was analyzed, and the missing data was filled by simple linear regression. A 6-month time scale was adopted for the method; the data was organized in a moving cumulative distribution of precipitation and applied to the Standardized Precipitation Index (SPI). In the application of the method, the cumulative values are processed into a normal distribution with the mean zero and variance one. That way, a drought event begins when the cumulative precipitation in the historical data series reaches an SPI value smaller than or equal to -1.00. Between 22 and 26 events for the stations of the sub-basin 37, and between 18 and 22 events for the stations of sub-basin 38 were identified. Medium-term tendencies were observed, with the occurrence of events every year or two, proving certain seasonality. The obtained values were then transformed into a return period of 20 years, and an isohyetal map was developed with the purpose to show the spatial variation of the event precipitation. By the outlined map, becomes evident an area of higher precipitation rates, situated on the coast along the states, and a drier region, located in the inland territory.